Patients Rate Physician Communication About Lung Cancer - Nelson, Judith E. (2011)
BACKGROUND: High-quality lung cancer care includes physician-patient communication about the disease and treatment, patient needs/preferences, and care goals. In this study, the authors evaluated communication with patients at all stages across multiple topics. METHODS: A standardized questionnaire asked patients with lung cancer to rate (on 5-point, verbal descriptor scale) the extent of communication with physicians on symptoms, spiritual concerns, practical needs, proxy appointment, living will preparation, prognosis, care goals, potential complications of therapy, life support preferences, and hospice. Communication was defined as inadequate if the patient reported discussing ≥5 of 11 questionnaire topics “not at all” or “a little bit.” Multivariate logistic regression was used to evaluate the factors associated with inadequate communication. RESULTS: In total, 276 of 348 (79%) eligible patients were enrolled (mean age [±standard deviation], 65 ± 10 years; 55% white, 21% black, and 19% Hispanic; all disease stages). For most topics, the majority of respondents reported that physicians communicated “not at all” or “a little bit.” Low ratings were frequent for discussion of emotional symptoms (56%; 95% confidence interval [CI], 49%–62%), practical needs (71%; 95% CI, 65%–76%), spiritual concerns (80%; 95% CI, 75%–85%), proxy appointment (63%; 95% CI, 57%–69%), living will preparation (90%; 95% CI, 85%–93%), life support preferences (80%; 95% CI, 75%–84%), and hospice (88%; 95% CI, 86%–94%). Communication was inadequate for patients of different ages, stages, and races, although Hispanics were less likely than non-Hispanic whites and blacks to report inadequate communication (odds ratio, 0.31; 95% CI, 0.15–0.65). CONCLUSIONS: Across all stages, patients with lung cancer reported low rates of physician-patient communication on key topics, which may increase patient distress, impair decision-making, and compromise clinical outcomes and use patterns.